Study On Parameters and Operating Modes of the Device for Deseeding Flax in the Field - V. G. Chernikov; R. A. Rostovtsev; S. V. Solov’ev (Сельскохозяйственные машины и технологии, 2021)
The authors showed that the main technological process in the combined and separate methods of fiber flax harvesting is deseeding or separating the seed part of the crop from the stems. It was confirmed that there is a direct impact of this process success on seed and straw losses, the fiber yield and quality, the heap composition, the labor intensity and energy consumption of flax drying and processing. (Research purpose) To develop a technology for stripping fiber flax with a comb deseeder during harvesting, to study the deseeder’s specifications and operating modes. (Materials and methods) The authors studied the technological process of stripping flax with a comb deseeder. An experimental plant of a comb deseeder was designed. A model of theoretical calculation was proposed based on the physical and mechanical properties of fiber flax and agrotechnical requirements for its harvesting. (Results and discussion) The authors theoretically determined the comb deseeder’s optimal height, operation kinematic mode, stripping cleanliness, the radius of the stripper drum. Laboratory studies were conducted. It was shown that threshing seeds in the field will reduce the loss of flax seeds by 10 per cent and the stem waste due to tangling during the harvesting process – by 18 per cent. It will also reduce the number of harvesting vehicles, personnel, and the cost of product. The authors identified an opportunity to increase productivity by increasing the width of the header grip: for example, the width of a grain harvester header is about 4 meters, and the width of a flax harvester header is 1.52 meters, that is, the productivity of flax harvesting will increase 2.6 times at the same speed, and 3 times at a higher speed. It was possible to eliminate one piece of equipment – a heap separating machine, since the technological operation of heap processing is carried out by a grain harvester. (Conclusions) The authors presented a theoretical substantiation of the comb deseeder’s operating parameters and modes for stripping fiber flax in the field. The authors proposed a model to determine them based on the physical and mechanical properties of flax and agrotechnical requirements for its harvesting.